Habeas corpus : from England to empire - Halliday, Paul D. (Paul Delaney), 1961- (Belknap Press of Harvard University Press, 2010)
A revisionist history of habeas corpus the world's most revered legal device. Habeas corpus was not established to protect the rights of the individual but rather to protect the individual from abusive judges and jailers.